Use of a decision support system improves the management of hemodynamic and respiratory events in orthopedic patients under propofol sedation and spinal analgesia: a randomized trial. - Zaouter, Cedrick; Wehbe, Mohamad; Cyr, Shantale; Morse, Joshua; Taddei, Riccardo; Mathieu, Pierre A; Hemmerling, Thomas M (Journal of Clinical Monitoring & Computing, 2014)
Decision support systems (DSSs) have been successfully implemented into clinical practice offering clinical suggestions and treatment options with excellent results in various clinical settings. Although their results appeared promising, showing that DSSs can increase anesthesiologists' vigilance and patient safety during surgery, DSSs have never been used before to help anesthesiologists in identifying critical events in patients under spinal analgesia with sedation. We have developed and clinically evaluated a DSS for this specific task. The DSS was developed with the ability to indicate respiratory and hemodynamic critical events via audio-visual alarms and give decisional aid. Critical respiratory events were defined as SpO2 <92 % and/or respiratory rate <8/min. Critical hemodynamic events were defined as mean arterial pressure (MAP) <60 mmHg and/or heart rate <40 bpm. The objective of this trial was to determine the duration to detect and treat these critical events with the help of the DSS (DSS Group) compared with a standard Control Group where the system was not in place. One hundred and fifty orthopedic patients undergoing spinal analgesia with propofol sedation were enrolled in this randomized control trial, 75 each group. All respiratory and hemodynamic critical events were detected in the DSS Group, while in the Control Group 26 % of the events were not detected.The delay to detect and treat critical events was significantly shorter (P < 0.0001) in the DSS Group at 9.1 ± 3.6 s, whereas 27.5 ± 18.9 s were necessary to identify them in the Control Group. There were no significant differences in physiological parameters in the two groups during surgery. The number of critical events/h occurring and the duration of surgery were similar in both groups. The number of hypoxemia episodes was significantly less (P = 0.036) in the DSS group (0.7 ± 1.0 vs. 1.4 ± 2.2 for the Control Group). The DSS tested in this trial could help the clinician to detect and treat critical events more efficiently and in a shorter length of time.